Strengthening A ‘Nepal, India, and China Equitable (NICE) Relationship’ for Regional Development - Kafle, Jagannath (The Journal of Economic Concerns, 2023)
This paper explores the prospects of fostering equitable trilateral economic cooperation among the contiguous nations of Nepal, India, and China (NIC). The underlying concept advocates for an integrated framework termed the 'Nepal, India, and China Equitable Relation' (NICE Relation). The study endeavours to elucidate Nepal's economic diplomacy from a geographical standpoint, emphasizing the significance of fostering warm neighbourhood relationships. Its overarching objective is to optimize the existing operational modalities of immediate neighbourhoods and socio-economic activities among NIC partners. The potential cooperations have unveiled insights derived from the realms of Development Cooperation, Economic Geography, and Centre-Periphery ideologies. A trilateral alliance of this nature has been revealed to catalyse enhanced cooperation within the immediate neighbourhood, fostering mutual benefits and contributing to the overarching goals of 'Protection (security), Peace, and Prosperity (PPP)' in the broader Himalayan region shared by these neighbouring nations.